Former Yugoslav Republic of Macedonia : Selected Issues Paper. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
The Macedonian labor market exhibits a high unemployment rate, yet does not demonstrate obvious and large enough constraints on the demand or supply side. Considerable achievements can be made by maintaining macroeconomic stability, attracting FDI, and closing the educational gaps. The second paper assesses ways in which the Macedonian financial sector could better contribute to growth and real convergence, taking stock of where the sector stands and its recent developments. Streamlining bankruptcy procedures, improving collateral and systematic collection and publication of real estate sales data, and revisiting the interest rate cap may serve to moderately boost credit supply.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet